Политико-административный интерфейс координирования действий местных органов власти в Бангладеш: обзор литературы - Рахман, Машиур; АсмиФахад; Насрин, Сальма (Вопросы государственного и муниципального управления, 2018)
The purpose of the study is to review the history of politicization in local government (LG) and determine the major factors that affect local coordination in Bangladesh maintaining the relationships between politics and administration under the changing provisions of the Upazila Parishad (UZP) Act of 2009 and the partisan LG provisions of 2015. The study is entirely based on a literature review where only qualitative data has been explored. Eighteen documents were selected as a data set through searching Web of Science, SCOPUS and Google Scholar databases by using the relevant key-words. The study found a number of factors that are outlined by inter- and intra-organizational perspectives which negatively effect on local coordination in Bangladesh. Among these factors, lack of proper division of work, financial dependency on central government, lack of a chain of command among LG bodies, and the compulsory advisory role of Member of the Parliament (MP) over UZP are found to be major inter-organizational factors, whereas dual loyalty of transferred departments, unequal project distribution among Union Parishads (UP), and the domination of non-elected members in UZP are also identified as intra-organizational factors that are negatively associated with local coordination. Despite these existing problems, recently adapted partisan LG provisions are also creating a huge conflict in not only the local administration but also in local politics. In this regard, the government will have a great opportunity to address these burning issues properly through removing these legal and practical barriers for ensuring better local coordination.